PERBANDINGAN KLITIKA DALAM BAHASA SASAK DENGAN KLITIKA DALAM BAHASA INDONESIA - Isnaeni, Mh (Jurnal Sasindo UNPAM, 2015)
AbstractThis article intends to describe the clitics used in Sasak along with the morphophonemic process which follows and then compare them to the Indonesian clitics.The data in this article were gathered through interview with some Sasak people as well as from the writerâ€™s insight as a native speaker of Sasak.            There are several pronominal clitics used in Sasak such as â€“n, -m, -t, -k, -de. The use of these Sasak clitics is followed by  morphophonemic changes such as addition and deletion of phonemes. After being compared to Indonesian clitics, it was found that There were similarities and differences between Sasak clitics and Indonesian clitics Key Words: Clitic, Morpophonemic change.